Systemic Administration of Exosomes Released from Mesenchymal Stromal Cells Promote Functional Recovery and Neurovascular Plasticity After Stroke in Rats. Issue 11 (November 2013) - Xin, Hongqi; Li, Yi; Cui, Yisheng; Yang, James J; Zhang, Zheng Gang; Chopp, Michael
Here, for the first time, we test a novel hypothesis that systemic treatment of stroke with exosomes derived from multipotent mesenchymal stromal cells (MSCs) promote neurovascular remodeling and functional recovery after stroke in rats. Adult male Wistar rats were subjected to 2 hours of middle cerebral artery occlusion (MCAo) followed by tail vein injection of 100 μg protein from MSC exosome precipitates or an equal volume of vehicle phosphate-buffered saline (PBS) ( n = 6/group) 24 hours later. Animals were killed at 28 days after stroke and histopathology and immunohistochemistry were employed to identify neurite remodeling, neurogenesis, and angiogenesis. Systemic administration of MSC-generated exosomes significantly improved functional recovery in stroke rats compared with PBS-treated controls. Axonal density and synaptophysin-positive areas were significantly increased along the ischemic boundary zone of the cortex and striatum in MCAo rats treated with exosomes compared with PBS control. Exosome treatment significantly increased the number of newly formed doublecortin (a marker of neuroblasts) and von Willebrand factor (a marker of endothelial cells) cells. Our results suggest that intravenous administration of cell-free MSC-generated exosomes post stroke improves functional recovery and enhances neurite remodeling, neurogenesis, and angiogenesis and represents a novel treatment for stroke.